Analysis Of Heirs' Responsibility For The Debt Of Debtors Who Have Deceived - Harialdi Dharmawan Syahputra; Hasim Purba; Rosnidar Sembiring; Tony, Tony (SEAN Institute, 2024)
Debts and receivables used for business have not produced results, and some businesses have even failed. This is where problems arise because the debtor cannot fulfill his obligation to repay the credit loan in question. Negligence or delay (whether intentional or unintentional) in credit payments will result in a fine which must be borne by the debtor as agreed, because the debtor cannot fulfill its obligations because the debtor has died. The legal research method used is empirical normative supported by interviews, with data collection by means of documentation studies, literature studies and interviews. The heir is responsible for the debtor's debt with the aim of providing legal protection to the creditor in providing credit to the debtor who then after signing the credit, the debtor has died, then this becomes the obligation of the heir to pay the heir's debt.